ANALISIS HASIL BELAJAR SISWA PADA MATERI PERBANDINGAN BERDASARKAN RANAH KOGNITIF REVISI TAKSONOMI BLOOM - Dwi Oktaviana; Iwit Prihatin (Universitas PGRI Adi Buana Surabaya, 2018)
This research to classify the most comparison and described the results of the study grade VII B students SMP Koperasi Pontianak the academic year 2017/2018, based on cognitive Revised Bloom’s Taxonomy. Research method used is descriptive method with a qualitative approach. The subjects of this research were students of class VII B with high and low ability levels. The instruments in this research were daily test questions and student answer sheets on the subject of comparison and interview guidelines. Based on the results of research, obtained the percentage classifications about 20% for understand (C2) and 80% for apply (C3). Students' mathematics learning outcomes based on cognitive domains Revised Bloom’s Taxonomy is that students are better able to solve problems with an understanding indicator of 60% than the problem with the indicator applying at 19.2%. Students with high ability to achieve indicators understand and apply while students with low abilities do not reach both indicators. Key Word: learning outcomes, ability level, revised bloom’s taxonomy, comparison